2016
DOI: 10.1111/1751-7915.12345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the composition of bacterial microbiota associated with the ruminal content, ruminal epithelium and in the faeces of lactating dairy cows

Abstract: SummaryThe objective of this research was to compare the composition of bacterial microbiota associated with the ruminal content (RC), ruminal epithelium (RE) and faeces of Holstein dairy cows. The RC, RE and faecal samples were collected from six Holstein dairy cows when the animals were slaughtered. Community compositions of bacterial 16S rRNA genes from RC, RE and faeces were determined using a MiSeq sequencing platform with bacterial‐targeting universal primers 338F and 806R. UniFrac analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 52 publications
30
96
0
Order By: Relevance
“…However, the abundance of Prevotella and Ruminococcus tended to be higher in the 2.5 AMSLF and the 7.50% AMSLF groups than in other treatment groups. Our results are in agreement with findings by Liu, Zhang, Zhang, Zhu, and Mao () who reported that Prevotella, Acetitomaculum Succiniclasticum, Saccharofermentans, Mogibacterium, and Ruminococcus were the dominant genera in ruminal content and the epithelium of lactating cows. The reason for increased in abundance of Prevotella and Ruminococcus in some treatment groups is unclear.…”
Section: Discussionsupporting
confidence: 94%
“…However, the abundance of Prevotella and Ruminococcus tended to be higher in the 2.5 AMSLF and the 7.50% AMSLF groups than in other treatment groups. Our results are in agreement with findings by Liu, Zhang, Zhang, Zhu, and Mao () who reported that Prevotella, Acetitomaculum Succiniclasticum, Saccharofermentans, Mogibacterium, and Ruminococcus were the dominant genera in ruminal content and the epithelium of lactating cows. The reason for increased in abundance of Prevotella and Ruminococcus in some treatment groups is unclear.…”
Section: Discussionsupporting
confidence: 94%
“…Microbiome studies of wild animals often use nonfresh fecal samples due to their noninvasive nature and inclusivity of the entire digestive tract (Li et al, ; Liu et al, ; Liu, Zhang, Zhang, Zhu, & Mao, ; Pope et al, ; Salgado‐Flores et al, ). Though contamination is a concern with nonfresh fecal samples, our study corroborates with findings from other muskox microbiome studies that used immediate fecal sampling (Andersen‐Ranberg et al, ; Ungerfeld et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted using the TIANamp Stool DNA Kit (Tiangen, Beijing, China) following the manufacturer’s instructions. The V3–V4 region of the bacterial 16S rDNA was amplified by PCR with a 20‐μl mixture containing 4 μl of 5 × FastPfu Buffer (TransGen Biotech, Beijing, China), 0.8 μl of 5 μM each primer (338F: ACTCCTACGGGAGGCAGCAG and 806R: GGACTACHVGGGTWTCTA AT) (Liu, Zhang, Zhang, Zhu, & Mao, ), 2 μl of 2.5 mM dNTPs, 0.4 μl of FastPfu Polymerase and 10 ng of template DNA. The PCR cycling conditions were as follows: 3 min of denaturation at 95°C followed by 27 cycles of 30 s at 94°C, 30 s at 55°C, and 45 s at 72°C, with a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%